PENERAPAN METODE KOOPERATIF DALAM PEMBELAJARAN NOTASI BALOK PADA KELAS VII-I DI MTSN TARUSAN - Yeni Yeni; Tulus Handra Kadir; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2013)
Abstract This article aims to explain and reveal how to raise students' motivation in learning notation in MTsN Tarusan. During this time the teacher is plagued with low student motivation, thereby disrupting the smooth teaching and learning. The research was conducted by qualitative research with descriptive methods. Data obtained by interviews, direct observation, library research, and documentation. The research instrument is the researcher himself as a key instrument. Data were analyzed with phenomenological techniques. Results of previous studies suggest that students lack motivation in learning notation, it is caused by lack of proper teaching methods by teachers in the art of music MTsN. After the change in the method by teachers in teaching the art of music notation, reveal positive results in improving student learning motovasi notation. Means cooperative method is able to change the level of student motivation towards learning in MTsN Tarusan notation. Through cooperative pembelajran methods students have the motivation to read notation, because the element of cooperation pembnelajaran important role in practice, so that students are able to help a fellow co weaknesses of the students themselves. Keywords: learning notation, and methods of cooperative learning